On Refinement of Bounds of Fractional Integral Operators Containing Extended Generalized Mittag-Leffler Functions - Ayşe Kübra Demirel (Sahand Communications in Mathematical Analysis)
In this paper, it is aimed to improvement the boundaries of fractional integral operators containing extended generalized Mittag-Leffler functions. The offered results enhance the previously known bounds of the distinct fractional integral operators for strongly $p$-convex functions of higher order. The acquired inequalities ensure boundedness, continuity, and Hadamard type inequality for fractional integrals containing an expanded Mittag-Leffler function. Furthermore, these results can be refined for various classes of strongly convex functions offered in the literature.